Small-area Estimates of General Practice Workforce Shortage in Rural and Remote Western Australia - Scott, J.; Larson, A.; Jefferies, F.; Veenendaal, Bert (Blackwell Publishing, 2006)
Objective: To trial a measure of rural and remote GP access for small areas. Design: A cross-sectional study using geographical information systems software to calculate GP to population rates with a floating catchment of 100?km radius around census collection districts (CCDs). Setting: Non-metropolitan Western Australia. Participants: The locations and full-time equivalents of GPs and other primary-care doctors were identified through a GP workforce survey. Main outcome measures: GP to population ratios for each CCD were classified as being above or below a benchmark of adequate GP access. CCDs with no GP sessions reported within 100?km were identified separately. These categories were investigated by divisions of general practice and by indigenous status, age and employment characteristics of the population. Results: Small-area estimates detected greater variation in access than depicted by conventional methods. Sixty-four per cent of the non-metropolitan population live in CCDs with adequate GP access. Forty-five per cent of indigenous people and 52% of people working in rural industries live in CCDs with access below the benchmark. Conclusions: The floating catchment method is a powerful tool to identify small areas of inadequate service. It can be applied to measure access to other professionals, medical equipment or facilities.